2010
DOI: 10.2807/ese.15.08.19496-en
|View full text |Cite
|
Sign up to set email alerts
|

A cluster of Legionnaires' disease caused by Legionella longbeachae linked to potting compost in Scotland, 2008-2009

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 6 publications
0
32
0
Order By: Relevance
“…Serum and respiratory secretions from patients with moderate to severe community-acquired pneumonia and no discernible cause should be sent for PCR and culture, particularly if the case has a connection to gardening (Pravinkumar et al, 2010). Earlier detection would reduce delays in targeted, optimal treatment, for while current empirical therapy for severe community-acquired pneumonia (a combination of a macrolide and a b-lactam) is active against Legionella species, animal studies and a recent systematic review and meta-analysis suggest that fluoroquinolones may have higher activity against Legionella species (Burdet et al, 2014;Pedro-Botet and Yu, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Serum and respiratory secretions from patients with moderate to severe community-acquired pneumonia and no discernible cause should be sent for PCR and culture, particularly if the case has a connection to gardening (Pravinkumar et al, 2010). Earlier detection would reduce delays in targeted, optimal treatment, for while current empirical therapy for severe community-acquired pneumonia (a combination of a macrolide and a b-lactam) is active against Legionella species, animal studies and a recent systematic review and meta-analysis suggest that fluoroquinolones may have higher activity against Legionella species (Burdet et al, 2014;Pedro-Botet and Yu, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…1). Previous studies have found that cases are commonly keen gardeners with exposure to plant-growing media (Pravinkumar et al, 2010;Potts et al, 2013). Indeed, in a survey of 24 bagged potting composts in the UK, 16 % of the plant-growing media contained L. longbeachae (Currie et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have investigated the diversity of Legionella species in compost (Steele et al, 1990;Hughes & Steele, 1994;O'Connor et al, 2007;Lindsay et al, 2009;Casati et al, 2009;Pravinkumar et al, 2010) and found a variety of species in high numbers, ranging from 10 3 to 10 5 c.f.u. g 21 .…”
Section: Discussionmentioning
confidence: 99%
“…A second paper in this issue describes a possible association between handling potting soil and infection with L. longbeachae [3]. As pointed out by the Scottish authors, this has long been well known and documented in Australia and New Zealand.…”
mentioning
confidence: 95%